Developing an Exercise Support Website using Human Pose Estimation - Nguyen, Phan Chi Phuong (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Data Science and Artificial Intelligence; 2020 - 2025